Detection rates of a national fetal anomaly screening programme: A national cohort study. (12th September 2022) - Aldridge, Nicholas; Pandya, Pranav; Rankin, Judith; Miller, Nicola; Broughan, Jennifer; Permalloo, Nadia; McHugh, Annette; Stevens, Sarah
Abstract: Objective: To measure condition‐specific detection rates for 14 physical conditions screened for by the NHS fetal anomaly screening programme (FASP) fetal anomaly (FA) ultrasound scan. Design: Retrospective audit of 12 694 diagnoses across a 3‐year national cohort. Setting: All English NHS and crown‐dependency hospital trusts providing maternity services. Population: Pregnancies booked for maternity services with an expected date of delivery between 1 April 2017 and 31 March 2020 and at least one diagnosis of a condition screened for by FASP. Methods: Active multi‐source ascertainment, linkage, audit and validation of clinical information to identify the subset of diagnoses meeting the condition‐specific positivity threshold for the FA scan. Main outcome measure: The accuracy of the FA scan compared with diagnostic reference standards. Results: FA scan detection rates were: anencephaly 96.3% (95% confidence interval [CI] 81.7–99.3%), atrioventricular septal defect: 69.2% (95% CI 65.8–72.4%), bilateral renal agenesis: 98.7% (95% CI 95.4–99.6%), cleft lip: 89.5% (95% CI 87.8–90.9%), congenital diaphragmatic hernia: 60.8% (95% CI 56.5–65%), Edwards syndrome: 73.8% (95% CI 67.5–79.3%), exomphalos: 59.4% (95% CI 49.4–68.7%), gastroschisis: 88.6% (95% CI 79–94.1%), hypoplastic left heart syndrome: 92.7% (95% CI 90–94.8%), lethal skeletal dysplasia: 93.2% (95% CI 88.6–96%), Patau syndrome: 82.3% (95% CI 72.4–89.1%), spina bifida: 93.8% (95% CI 91.8–95.3%), tetralogy of Fallot: 75.4% (95% CI 72.1–78.4%) and transposition of the great arteries: 84.9% (95% CI 81.7–87.5%). Conclusions: The performance of the FA scan is above the expectations set in 2010 for most conditions. For the remaining conditions, the majority of fetuses and babies affected are detected before the FA scan.